Strategi Peningkatan Mutu Pendidikan melalui Penerapan Total Quality Management (TQM) di Era Transformasi Digital - Diana, Zuhur; Faslah, Romi (Universitas Nusantara PGRI Kediri, 2025)
The quality of education in the era of digital transformation brings its own challenges for educational institutions to be adaptive to technological advances and changes in student needs. In reality, there are still many educational institutions that do not have a structured and sustainable quality management system. Total Quality Management (TQM) is present as a managerial instrument that helps educational institutions in managing educational services optimally in order to provide satisfaction to customers so that they can achieve the expected quality. This study aims to examine the strategy for improving the quality of education in the digital era through the implementation of TQM. The method used is a literature study by collecting sources from books or scientific articles that are relevant to the research theme. The results of the study show that the strategy for improving the quality of education in the digital era can be carried out by applying the principles of TQM which include a focus on customer satisfaction, appreciation for individual contributions, fact-based management, and continuous improvement. However, its implementation is inseparable from various challenges such as the digital literacy gap, resistance to change, and limited infrastructure facilities. Solutions that can be taken to overcome these challenges include digital literacy training, strengthening an adaptive culture, and providing adequate infrastructure. By implementing TQM optimally, educational institutions are expected to be able to build a quality and globally competitive learning system.